Progress in diagnostics of the urinary system diseases in children - Jung, Anna (Przewodnik Lekarza/Guide for GPs, 2011)
In last decade we observed significant progress in methods of urinary system imaging (egz. Doppler ultrasonography, computed tomography, magnetic resonance). New study presented laboratory markers of acute kidney injury detected in serum and urine. Within recent years many gene mutations responsible for symptoms of nephrotic syndrome have been described. Genetic tests in pediatric nephrology should be become a standards procedure in diagnostics of nephrotic syndrome resistance to treatment and in children under 1 year with nephrotic syndrome.